The Modeling Of Adaptive Neck Support System For Economy Class Aircraft Seat - Tan, Chee Fai; Chen, Wei; Sarban Singh, Ranjit Singh; Rauterberg, Matthias (2011)
With the rapid development of technology, the comfort of service has become an important issue. Air travels, especially long distance, may cause both physiological and psychological discomfort to passenger. Passenger comfort is a main factor in user’s acceptance of transportation systems. In order to improve the neck comfort during long haul air travel, an adaptive neck support system was developed and embedded in the economy class aircraft seat. In this paper, we describe the development of adaptive neck support system.